The Impact of Abū ’l-A‘lā Maudūdī and Jamā‘at-i Islāmī on the Intellectual Career of Maryam Jameelah - Ahmad, Zohaib (Islamic Studies, 2020)
Maryam Jameelah (1934–2012) was a Jew by birth, but she embraced Islam as her final religion. In 1962, on the invitation of Abū ’l-A‘lā Maudūdī (1903–1979), she migrated to Pakistan. The literature shows that she was influenced by the works of Maudūdī and supported his politico-religious movement, Jamā‘at-i Islāmī. The present study, however, argues—based on the analysis of her published and unpublished works—that her writing career can be divided into two phases. In the first phase (roughly from 1962 to 1969), she supported Maudūdī and his mission while in the second phase (1969–2012), she started controverting his ideas and criticized his certain views, considering him an advocate of modernism. Thus, on the one hand, she regarded him as a mujaddid of his time, but on the other hand, she considered him a supporter of evolutionism and progressivism, who had contempt for the tradition. This paper further highlights that though her writings appear to support Jamā‘at-i Islāmī, but she never became a formal member of it or any other movement during her stay in Pakistan.